Design and Fabrication of Orthokeratology Lens with Multi-Linear and Spherical Aberration Corrected for Myopia Control - Zhengwang Li; Ruijin Hong; Dawei Zhang (Photonics)
Myopia, an increasingly grave public health concern, necessitates the implementation of various techniques for its management. These techniques predominantly comprise the employment of spectacles correction, orthokeratology (ortho-k), and soft bifocal and multifocal lenses. In the present study, a pioneering polish-free ortho-k lens was devised, featuring two reverse lines and three alignment lines, which, respectively, expedite the shaping process and enhance centration. The structural blueprint of the ortho-k lens, along with the simulation of fluorescence staining, was executed employing the FocalPoints software V7.0 (Advance Medical, Milan, Italy). Subsequently, lens aberration elimination was accomplished through ray tracing utilizing ZEMAX software V13.0 (Focus Software, Wixom, MI, USA). The fabrication of the lens was carried out via high-precision lathe turning using the UPC 100 Vision instrument (SCHNEIDER, Ratingen, Germany). The power profile of the ortho-k lens was measured using the CONTEST 2 apparatus (ROTLEX, Omer, Israel). The surface quality was observed under a 200× microscope (ZEISS, Oberkochen, Germany). The fitting of the lens was assessed through the utilization of both Slit-lamp microscopy (MediWorks, Shanghai, China) and Corneal topographer (Medmont E300, Melbourne, VIC, Australia)